Association Between Serum Selenium Levels with Rheumatoid Arthritis - Yu, Na; Fang Han; Xiaojun Lin; Chun Tang; Jinghua Ye; Xiaoyan Cai (Biological trace element research, 2016)
There are conflicting reports on the correlation between serum selenium (Se) levels with rheumatoid arthritis (RA). Through a meta-analysis approach, the aim of the present study is to clarify the relationship between serum Se levels with RA. We searched literatures that met our predefined criteria in PubMed, ScienceDirect, and OVID published as of September 2015. Ten eligible articles with 14 caseâcontrol studies involving 716 subjects were identified. Overall, pooled analysis indicated that subjects with RA had lower serum levels of Se than the healthy controls (standardized mean difference (SMD)â=ââ1.347, 95Â % confidence interval (CI)â=â[â1.872, â0.823], pâ